Static solutions in Einstein-Chern-Simons gravity. Issue 6 (28th June 2016) - Crisóstomo, J.; Gomez, F.; Mella, P.; Quinzacara, C.; Salgado, P.
Abstract: In this paper we study static solutions with more general symmetries than the spherical symmetry of the five-dimensional Einstein-Chern-Simons gravity. In this context, we study the coupling of the extra bosonic field h a with ordinary matter which is quantified by the introduction of an energy-momentum tensor field associated with h a . It is found that exist (i) a negative tangential pressure zone around low-mass distributions ( μ < μ1 ) when the coupling constant α is greater than zero; (ii) a maximum in the tangential pressure, which can be observed in the outer region of a field distribution that satisfies μ < μ2 ; (iii) solutions that behave like those obtained from models with negative cosmological constant. In such a situation, the field h a plays the role of a cosmological constant.